Use of different surface covering materials to enhance removal of radiocaesium in plants and upper soil from orchards in Fukushima prefecture. (January 2019) - Sato, Mamoru; Akai, Hiroko; Saito, Yuichi; Takase, Tsugiko; Kikunaga, Hidetoshi; Sekiya, Nobuhito; Ohtsuki, Tsutomu; Yamaguchi, Katsuhiko
Abstract: The effectiveness of a decontamination methodology whereby herbaceous plants were grown through different materials covering the soil surface followed by subsequent removal of the material, associated plant tissues and attached soil on 137 Cs removal from soil was evaluated. Revegetation netting sown with Kentucky bluegrass and white clover had a high effectiveness in 137 Cs removal when rolling up the plants, roots, and rhizosphere soil approximately 6 months after sowing. The removal rate was lower when there was higher 137 Cs vertical migration down the soil profile. The maximum removal effectiveness of 93.1% was observed by rolling up fertilized Kentucky bluegrass with a well-developed root mat without netting, indicating that applying nutrients to encourage the development of roots or root mats in the 3 cm topsoil rhizosphere is an efficient technology to increase the decontamination effect of plant removal in orchards. Netting and weeding were able to remove up to 80% of 137 Cs in the soil without the use of heavy machinery. There was a significant relationship between the removal ratio and the removed soil weight per area. Using the relationship on the site below the canopy, removal of 14.3 kg m −2 DW soil would achieve a removal ratio of 80%. The effectiveness of the technique will decrease with time as radiocaesium migrates down the soil profile but this would be expected to occur slowly in many soils. Highlights: The effectiveness of removal of the netting covering the soil surface, plants grown through nettings and attached soil on 137 Cs removal from soil was evaluated. Significant correlations were observed between removal ratio of 137 Cs and mass of soil removed. Netting and weeding are able to remove up to 80% of 137 Cs in the soil without using heavy machinery. The effectiveness of 137 Cs removal is a function of the 137 Cs depth profile and the density of the roots developed by the undergrowth.